The design and development of small electric vehicles (EV) using power inverter based AC motor - Rashid, Muhammad Mahbubur; Molik, Md. Sazib; Rahman, Mohammed Ataur; Jahiman, Mohd Azmin (2014)
In this study explain about the design and development of small electric vehicles (EV) using power inverter. The goal of this study is to develop the low cost electric vehicles which use energy most efficiently. The major features of this prototype are the power take-off system frame design and the control system. In this paper, DC power will convert to AC power for AC motor drive of the electric vehicles. The design and accessories of this electric vehicle are including chassis, battery, controller and motor. In this paper also need to identify the advantages of the electric vehicles in terms of environment, energy and cost. Moreover, this study also focused to compare the performance of electric vehicle with DC powered, AC powered and engine.